Ezra's social drama: identity formation, marriage and social conflict in Ezra 9 and 10 - Moffat, Donald P. (Library of Hebrew bible/Old Testament studies, 2013)
Moffat aims to provide further insight into the mixed marriage narrative by exposing the social and cultural factors on which it is based. He also identifies historical traces in the narrative that can contribute to an historical reconstruction of the post-exilic era